Peran pendidikan keagamaan dalam membentuk modal manusia masyarakat Muslim di Patani - Murnee Masae; Nurochim; Sita Ratnaningsih (Universitas Widya Mataram, 2026)
Religious education in Patani, Southern Thailand, plays a strategic role in preserving the Malay-Islamic identity and shaping the character of the minority Muslim community. Although its socio-political role has been extensively studied, there remains a disconnect between the traditional functions of Islamic educational institutions and the economic parameters of human capital development. This study aims to analyze the contribution of religious education to shaping the human capital of the Patani Muslim community, focusing on moral aspects, social competence, and literacy skills. Using a qualitative descriptive method with a literature review approach, this study evaluates the role of Islamic boarding schools (pesantren), madrasahs (Islamic schools), and modern Islamic schools. The results indicate that religious education significantly influences the formation of non-economic human capital through the internalization of morals, discipline, and Arabic and Jawi literacy. However, gaps are found in the integration of technical and academic skills required by the modern labor market. In conclusion, religious education is a key foundation of human capital in Patani, but requires curriculum transformation and strengthened collaboration with national policies to enhance its effectiveness in community economic empowerment.